Unregulated lending, mortgage regulations and monetary policy - Ugochi Emenogu; Brian Peterson (Bank of Canada, 2022)
Macroprudential policies are often aimed at the traditional banking sector while nondepository financial institutions or shadow banks have limited or no prudential regulations. This paper studies the macroeconomic impact of household-side macroprudential tightening in the presence of unregulated lenders. Our result shows that the presence of unregulated lenders dampens the impact of the policies on house prices and household debt. We also find that leakage to the unregulated sector increases when monetary policy is tightened.
Keywords: E44; E50; E52; E58; G21; G23; G28; 330; Monetary policy transmission; Financial institutions; Financial system regulation andpolicies